HUBUNGAN RIWAYAT KONTAK PENDERITA TUBERKULOSIS PARU (TB) DENGAN KEJADIAN TB PARU ANAK DI BALAI PENGOBATAN PENYAKIT PARU-PARU (BP4) PURWOKERTO - Yulistyaningrum, .; Sri Rejeki, Dwi Sarwani (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2010)
Background:  Tuberculosis (TB) is chronic communicable disease that caused byMycobacterium tuberculosis. Nowadays, TB still becomes an important health problem. In Indonesia, every year there are 1,3 million children under 15 years old have infected M. tuberculosis and 450.000 children died because of TB. Based on the age-based diagnose report, a percentage of TB patients on child group (0-14 years old) in year 2009 at BP4 Purwokerto was equal 26,42%. This condition was  probably happened due to any contact inside a house with adult TB sufferers. The objective of this research is to find out the association between the contact history of TB and the occurrence of pulmonary TB on a child group at BP4 Purwokerto.Method : This was an observational analytic research with cases control approach. The numbers of samples are 76 children divided into 38 cases and 38 controls. Cases were children patients who were 0-14 years old, clinically diagnosed as TB sufferer and confirmed by the result of x-ray test that showed sugestif description at BP4 Purwokerto. Controls were children patients who were 0-14 years old, clinically diagnosed as not TB sufferer and confirmed by the result of x-ray test that not showed sugestif description at BP4 Purwokerto. Data were analyzed by using the methods of univariate, bivariate (Chi-Square test and Mantel Haenszel test).Result :  The result of this research showed that the contact history of TB had a significant association with the occurrence of pulmonary TB on child group at BP4 Purwokerto without influenced by economic status, BCG scar status and availability of smoker inside a house (P = 0,001; OR = 6,378; 95%CI 2,151-18,918). To prevent the occurrence of pulmonary TB on a child, parents should keep away their children from direct contact with adult TB sufferers trough separating them temporarilly.Keywords : History of contact TB, Pulmonary TB on child Bibliography : 76 (1961-2010)